Phase Transitions of Binary Lipid Mixtures: A Combined Study by Adiabatic Scanning Calorimetry and Quartz Crystal Microbalance with Dissipation Monitoring. (20th January 2015) - Losada-Pérez, P.; Mertens, N.; de Medio-Vasconcelos, B.; Slenders, E.; Leys, J.; Peeters, M.; van Grinsven, B.; Gruber, J.; Glorieux, C.; Pfeiffer, H.; Wagner, P.; Thoen, J.
Abstract : The phase transitions of binary lipid mixtures are studied by a combination of Peltier-element-based adiabatic scanning calorimetry (pASC) and quartz crystal microbalance with dissipation monitoring (QCM-D). pASC, a novel type of calorimeter, provides valuable and unambiguous information on the heat capacity and the enthalpy, whereas QCM-D is proposed as a genuine way of determining phase diagrams by analysing the temperature dependence of the viscosity. Two binary mixtures of phospholipids with the same polar head and differing in the alkyl chain length, DMPC + DPPC and DMPC + DSPC, are discussed. Both techniques give consistent phase diagrams, which compare well with literature results, showing their capability to map the phase behaviour of pure lipids as well as lipid mixtures. This work can be considered as a departure point for further investigations on more complex lipid mixtures displaying relevant phases such as the liquid-ordered phase and solid-lipid interfaces with biologically functional importance.